2008
DOI: 10.1111/j.1600-0781.2008.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Polypodium leucotomos inhibits ultraviolet B radiation‐induced immunosuppression

Abstract: The ability of PL to inhibit UVB radiation-induced immune suppression may explain, in part, its ability to inhibit UVR-induced skin cancer induction in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Previous studies reported that oral PL administered in single doses decreased UVR-induced damage in human skin (12, 13) and Alcaraz et al (14), in a pilot study, observed that topical application of a PL extract reduced the number of mice presenting tumors after UVB irradiation. Mulero et al (15) reported an immunoprotective effect of oral PL after UV irradiation in rats and Siscovick et al (16) demonstrated that oral PL prevented local and systemic photoimmunosuppression in a murine model which could explain, at least in part, its ability to inhibit UVR-induced skin cancer. Thus, we demonstrate for the first time the cutaneous antitumorigenic properties of PL given by oral route, using an experimental UVR-tumorigenic model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that oral PL administered in single doses decreased UVR-induced damage in human skin (12, 13) and Alcaraz et al (14), in a pilot study, observed that topical application of a PL extract reduced the number of mice presenting tumors after UVB irradiation. Mulero et al (15) reported an immunoprotective effect of oral PL after UV irradiation in rats and Siscovick et al (16) demonstrated that oral PL prevented local and systemic photoimmunosuppression in a murine model which could explain, at least in part, its ability to inhibit UVR-induced skin cancer. Thus, we demonstrate for the first time the cutaneous antitumorigenic properties of PL given by oral route, using an experimental UVR-tumorigenic model.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using rodent models have revealed that PL blocks UVB-induced immunosuppression [36]. PL prevents the elimination of Langerhans cells induced by UV irradiation during direct UV exposure [35], or PUVA-therapy [28].…”
Section: Fernblock: a Multi-pronged Approach To Photoprotectionmentioning
confidence: 99%
“…Moreover, PL was also able to suppress the production of ROS that was induced by UV, therefore acting as antioxidant agent (Gonzalez et al, 2011). In addition, orally administered PL to mice resulted in inhibition of UVB radiation that triggered skin cancer (Siscovick et al, 2008).…”
Section: Fernmentioning
confidence: 99%